Demonstration of catalytic properties of de-inking sludge char as a carbon based sacrificial catalyst - Fivga, Antzela; Jahangiri, Hessam; Bashir, Muhammad Asif; Majewski, Artur J.; Hornung, Andreas; Ouadi, Miloud (Journal of Analytical and Applied Pyrolysis, 2020)
De-inking sludge (DIS) is generated as a waste stream from secondary fibre paper mills during the de-inking stage of the paper pulping process; in order to ensure end of waste to landfill an alternative valorisation route is required for this waste. At the same time, an inexpensive sacrificial catalyst is essential to achieve the techno-economic feasibility of biomass gasification and pyrolysis. The present work explores the potential of DIS char as a catalyst using a 2 kg/h Thermo-Catalytic Reforming (TCR®) system, which involves intermediate pyrolysis combined with a unique integrated catalytic reforming step. Wood was used for the TCR catalytic experiments with a DIS char to biomass ratio (wt.%) of 0.3:1 and 0.65:1. Results have shown that hydrogen relative volumes and syngas yields, are positively correlated with the increase in DIS char to wood ratio. Average hydrogen relative volumes of 28.30 vol.% and syngas yields of 47.64 wt.% were achieved. Organic liquid yields were significantly reduced in favour of higher syngas yields, implying the suitability of DIS char as a tar reduction catalyst in gasification or pyrolysis. The influence of TCR DIS char is less profound on the chemical distribution in the organic phase of bio-oil; a reduction on PAHs from 38.82 % to 26.70 % though was determined with the use of DIS char, according to the relative abundance peak areas from the GC–MS chromatograms. The oxygen content of bio-oil was significantly reduced due to cracking of higher molecular weight organics.
CRIS-Team Scopus Importer:2020-01-24
Keywords: Bioenergy; Catalyst; Char; De-inking sludge; Paper industry; Pyrolysis